STUDY OF CATALYTIC CYCLISATION OF (+)-CITRONELLAL WITH Zn/γ-ALUMINA AS CATALYST - Elvina Dhiaul Iftitah; Hardjono Sastrohamidjojo; M. Muchalal (Universitas Gadjah Mada, 2004)
The reaction of catalytic cyclisation of (+)-citronellal has been done using g-alumina and Zn/γ-alumina as catalysts. Zn/γ-alumina catalyst was prepared by impregnation of ZnBr2 into solid of γ-alumina in methanol as a solvent. The calcination process is performed on Muchalal reactor at 400 oC. The reactions were carried out under nitrogen gas atmosphere by mixing 5 mL sample and 1.0 g catalyst at 90-95 oC for 3 hours. The product of reaction was analyzed using GC, FT-IR and GC-MS. The reaction of cyclization of (+)-citronellal with γ-alumina catalyst did not give targeted product as well as reaction with Zn/g-alumina catalyst. Whereas, the reactions with Zn/γ-alumina catalyst gave four compounds of isopulegol stereoisomer. Conversion of (-)-Isopulegol, (+)-Neoisopulegol, (+)-Isoisopulegol and (+)-Neoisoisopulegol were 64,29%, 18,80%, 9,20% and 3,32% respectively. For that reason, the transformation of (+)-sitronelal using Zn/γ-alumina was considered to be the best catalyst. A reaction mechanism is proposed where the (+)-citronellal molecule binds to a catalyst Lewis acid site via the aldehyde oxygen and the π-electrons of the double bond. Subsequent protonation of the aldehyde via a neighbouring Bronsted acid site initiates the cyclisation to isopulegol.